Pengaruh Indeks Volatilitas, Nilai Tukar dan Pertumbuhan Ekonomi Terhadap Integrasi Pasar Modal ASEAN Dengan Pasar Modal Amerika Serikat - Nila Listiana; Robiyanto (Politeknik Caltex Riau, 2021)
There are many variables which will be influencing capital market integration. Some of those variables are come from external factor, such as Volatility Index (VIX), exchange rate, and economic growth. This study aims to analyze the effect of VIX, exchange rate, and economic growth to the integration of ASEAN capital market and United States capital market. The data was collected from secondary data in the form of VIX quarterly data, exchange rate, economic growth, ASEAN capital market such as Indonesia (JKSE), Singapore (STI), Philippines (PSEi), Thailand (SETi), Malaysia (KLCI), and United States capital market (DJIA) during the first quarter from 2005 to third quarter 2020. Further, the data was analyze by using DCC GARCH method was used to see the dynamic correlation between ASEAN capital market and US capital market. Hence, GARCH method to examine the effect of changes in VIX, exchange rate, and economic growth for ASEAN capital market and US capital market. The result showed a positive dynamic correlation between ASEAN capital market and US capital market, the presence of VIX and exchange rate has significant effect for ASEAN capital market and US capital market, while economic growth only has significant effect to the integration of STI.